Evaluation method of high-purity quartz ore source for photovoltaic crucible

Through a multi-dimensional comprehensive evaluation method, combined with ICP-OES, FTIR, polarization microscope and electronic probe detection, a comprehensive evaluation of the quartz mineral source was solved, and the problems of defoaming and dehydration efficiency during the separation and flotation of quartz sand in the existing technology were solved, and accurate judgment and improvement of the quality of quartz mineral source was achieved.

CN119757320APending Publication Date: 2025-04-04PUCHENG TELEJING TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411864416.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When the existing flotation device performs flotation operations, it is not convenient to realize multiple multiple flip flotation during quartz sand separation, rapid defoaming and rapid dehydration of quartz sand liquid during flotation.

Method used

A multi-dimensional comprehensive evaluation method was adopted, combining four methods: ICP-OES detection, FTIR detection, polarization microscopy detection and electronic probe detection to conduct a comprehensive evaluation of quartz mineral sources.

Benefits of technology

A more accurate judgment of the quality of quartz mineral sources has been achieved, the evaluation distortion problem in the existing technology has been solved, and the accuracy of quality evaluation of quartz mineral sources has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119757320A_ABST
    Figure CN119757320A_ABST
Patent Text Reader

Abstract

The invention relates to a method for evaluating high-purity quartz ore for a photovoltaic quartz crucible, which comprises the following steps of: S1, cleaning the surface of a blocky quartz raw material, crushing the blocky quartz raw material into a powder raw material, digesting the powder raw material by hydrofluoric acid and nitric acid, and detecting the content of metal impurity elements by using ICP-OES (Inductively Coupled Plasma Optical Emission Spectrometer) equipment; s2, cleaning the surface of the blocky quartz raw material, cutting the blocky quartz raw material into slices, polishing the surface, and carrying out FTIR infrared spectrum detection; s3, cleaning the surface of the blocky quartz raw material, cutting the blocky quartz raw material into slices, polishing the surface, and carrying out polarizing microscope detection; and S4, cleaning the surface of the blocky quartz raw material, cutting the blocky quartz raw material into slices, polishing the surface, and carrying out electronic probe detection. Therefore, a quartz ore source evaluation system is established and perfected, and high-purity quartz ore suitable for being used as a photovoltaic quartz crucible raw material is more efficiently and accurately selected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quartz ore, in particular to an evaluation method for a high-purity quartz ore source for a photovoltaic crucible. Background Art

[0002] With the adjustment of the global energy structure and the rapid development of the photovoltaic industry, photovoltaic crucibles, as an indispensable key component in the photovoltaic industry chain, are becoming increasingly important. Quartz crucibles, as essential containers for the production of silicon single crystals, play a vital role in the photovoltaic industry. However, the quality and performance of quartz crucibles are directly affected by their raw materials, quartz ore, and the quartz ore source evaluation system has become an important cornerstone for ensuring the quality of photovoltaic crucibles.

[0003] As a key container for the growth of photovoltaic single crystal silicon, the quality of quartz crucible directly affects the purity and quality of single crystal silicon. The purity, impurity content, particle size and other factors of quartz minerals will significantly affect the performance of quartz crucibles. For example, excessive impurity content will cause deformation and crystallization of the crucible, which will in turn affect the growth efficiency and quality of single crystal silicon. Therefore, it is of great significance to establish a scientific and comprehensive quartz ore source evaluation system to ensure the quality of quartz from the source, which is of great significance to improving the performance and reliability of photovoltaic crucibles.

[0004] With the rapid development of the photovoltaic industry, the demand for photovoltaic crucibles has continued to increase, and higher requirements have been placed on the quality and performance of crucibles. By establishing and improving the quartz ore source evaluation system, the development of the domestic high-purity quartz sand industry can be promoted, the dependence on imports can be reduced, and the competitiveness of domestic photovoltaic crucibles can be enhanced. At the same time, this will also promote the overall technological and industrial upgrading of the photovoltaic industry and realize the independent control of the photovoltaic industry chain. Summary of the invention

[0005] The present invention aims at the technical problems existing in the prior art and provides a sink-float separation device for quartz sand production to solve the problem that the existing flotation device is not convenient for realizing multiple and multiple flip-over flotation during quartz sand separation and rapid defoaming and impurity removal during the flotation process and rapid dehydration of quartz sand liquid.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] Carry out "Powder Sample Preparation" as shown in the figure, clean the surface of the block quartz raw material and crush it into powder raw material, and carry out "ICP-OES Test" as shown in the figure. After digestion with hydrofluoric acid and nitric acid, the sample is tested for the content of metal impurity elements using ICP-OES equipment;

[0008] As shown in the figure, "thin slice sample preparation" is performed, the surface of the block quartz raw material is cleaned, cut into slices and the surface is polished, as shown in the figure, "FTIR detection" is performed, and infrared spectrum detection is performed using a Fourier transform infrared spectrometer;

[0009] Carry out "Polarizing microscope sample preparation" as shown in the figure, clean the surface of the block quartz raw material, cut it into slices and polish the surface, and carry out "Polarizing microscope detection" as shown in the figure to analyze and calculate the size and density parameters of gas-liquid inclusions;

[0010] Perform "electron probe sample preparation" as shown in the figure, clean the surface of the block quartz raw material, cut it into slices and polish the surface, and perform "electron probe detection" as shown in the figure to analyze and calculate the impurity mineral composition and morphology.

[0011] The mesh size of the crushed powder material is between 40-1000 meshes.

[0012] The impurity elements detected include aluminum, boron, chromium, manganese, iron, copper, potassium, lithium, sodium, nickel, magnesium, calcium, titanium, zirconium and phosphorus; the element content detection range is between 0.1-200ppm.

[0013] The thickness of each quartz slice is measured and the preferred thickness is 1-5 mm.

[0014] The dried ore slices were tested using a Fourier transform infrared spectrometer in the wavelength range of 1000-4000. The hydroxyl determination formula is, -ln(T) = kdC,

[0015] In the formula,

[0016] T is the transmittance of the quartz ore slice;

[0017] k is a constant that is related to the properties of the absorbing substance and the wavelength of the incident light;

[0018] d is the thickness of the specimen, in millimeters (mm) for each piece;

[0019] C is the hydroxyl content of the sample, expressed in micrograms per gram.

[0020] The thin slice is polished with polishing papers and polishing cloths of different meshes, preferably with polishing cloths of 200 mesh, 6000 mesh, 1200 mesh and 2000 mesh, respectively.

[0021] The preferred thickness for each quartz slice is 50-300 μm.

[0022] Polarized light microscopy is measured using transmitted polarized light.

[0023] Analyze the occurrence state of impurity minerals, including strips, dots, lines, layers and blocks, etc.

[0024] Calculate the element ratio of impurity minerals in quartz slices and then determine the mineral composition.

[0025] The present invention provides a method for comprehensively evaluating quartz ore sources in multiple dimensions.

[0026] In the prior art, the evaluation of quartz ore sources for photovoltaic crucibles is limited to a single evaluation method, which will result in evaluation distortion and fail to accurately judge the quality of the quartz ore sources. The present invention integrates ICP-OES detection, FTIR detection, polarizing microscope detection and electron probe detection, and uses multi-dimensional parameters to comprehensively evaluate the quartz ore sources, which can more accurately judge the quality of the quartz ore sources. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The system of quartz ore source evaluation methods is shown in the figure.

[0028] The surface of the quartz ore sample was cleaned according to the process sequence, and then the sample preparation and testing were carried out in the following four dimensions, including ICP-OES testing, FTIR testing, polarizing microscope testing and electron probe testing.

[0029] Finally, statistical calculation and analysis results are performed. DETAILED DESCRIPTION

[0030] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0031] Clean the ore surface; use surfactant to wash away the clay attached to the ore surface, then rinse with deionized water and dry;

[0032] Use a wire cutting machine to cut the ore into suitable sizes, put it into a ball mill for grinding, and process the ore into a powder sample;

[0033] Weigh an appropriate amount of quartz powder sample, put it into a digestion tank, add mixed acid, assemble the digestion tank and put it into a microwave digestion instrument for digestion; after the digestion is completed, carry out acid removal treatment and set aside for use after the treatment is completed;

[0034] Configure the standard series of metal element working solutions: 0.05, 0.1, 0.2, 0.5, 1.0 mg / L. The metal elements include: aluminum, boron, chromium, manganese, iron, copper, potassium, lithium, sodium, nickel, magnesium, calcium, titanium, zirconium;

[0035] Add 10 ml of constant volume solution to the sample after acid removal treatment. After constant volume, use ICP-OES to detect the metal ions in the sample. The instrument will automatically calculate the results.

[0036] Cutting the cleaned quartz ore and cleaning the cut ore slices;

[0037] Grinding and polishing the surface of the cleaned ore slices;

[0038] Drying the ore flakes to remove moisture from the surface of the flakes;

[0039] The dried ore slices were tested using a Fourier transform infrared spectrometer in the wavelength range of 1000-4000;

[0040] Determine the parts that need to be ground to ensure that the sample is representative and can reflect its overall characteristics;

[0041] Use a wire saw to cut the sample into thin slices of appropriate size.

[0042] The sample was placed on a grinder and initially ground using 200# sandpaper until the sample thickness was reduced to approximately 0.1-0.15 mm.

[0043] Use finer sandpaper (600#, 1200#, 2000#) to grind until the sample thickness reaches about 0.03mm. During the grinding process, observe the light transmittance of the sample at any time to ensure that the thickness is uniform and there are no obvious scratches.

[0044] Use alcohol or other solvents to clean the remaining impurities around the sheet to keep the sheet clean.

[0045] Use a polarizing microscope to observe the distribution of gas-liquid inclusions in the sample. For each ore sample, ten photos at different positions should be taken to count the number of gas-liquid inclusions.

[0046] Use analysis software to calculate and count the number, size and distribution of gas-liquid inclusions in microscopic photos;

[0047] Use a cutting machine to cut the quartz ore into blocks of appropriate size for subsequent processing.

[0048] Use epoxy resin mounting material to embed the sample to ensure that the sample is not easy to fall off or deform during subsequent processing.

[0049] Place the sample in the mold, add the appropriate amount of epoxy resin, and stir thoroughly to ensure that the sample is evenly distributed. Then, place the mold in a constant temperature box for curing, so that the epoxy resin can fully harden and firmly fix the sample.

[0050] Perform a preliminary grinding of the mounted sample using coarse-grit sandpaper or abrasive to remove surface irregularities and excess epoxy.

[0051] Gradually use finer sandpaper or abrasives for fine grinding until the sample surface reaches the required flatness. During this process, pay attention to controlling the grinding force and speed to avoid damaging the sample.

[0052] Polish the sample surface with a polisher and polishing agent to obtain a smooth, scratch-free surface. During the polishing process, pay attention to controlling the polishing time and intensity to ensure that the sample surface reaches nanometer-level flatness.

[0053] Use a vacuum coating machine to evenly evaporate carbon on the sample surface. During the coating process, it is important to control the coating thickness and uniformity to ensure that the sample surface has good electrical and thermal conductivity.

[0054] The processed samples are placed in an electron probe sample chamber for electron probe and spectrum detection;

[0055] The types of impurity minerals contained in the sample are analyzed based on the images and spectral data taken by the electron probe.

[0056] The fuzzy hierarchical evaluation method is used to perform quantitative calculations on the data obtained in the above steps to achieve a comprehensive evaluation of the quartz ore source and to achieve horizontal quantitative comparison of the quality of the quartz ore source. Specific embodiment:

[0058] The I CP-OES test results of sample 1 were 377ppm aluminum, no boron detected, no chromium detected, 0.8ppm manganese, 14ppm iron, 22ppm copper, 68.9ppm potassium, no lithium detected, 90.4ppm sodium, no nickel detected, 7.5ppm magnesium, 3ppm calcium, 63ppm titanium, and 16ppm zirconium. The infrared spectrum test results showed that the hydroxyl content was 140.9ppm. The polarizing microscope test results showed that the gas-liquid inclusions were 0-10μm (>30) / mm 2 , 10-20μm(>15) / mm 2 ; The results of electron probe test showed that quartz contained a large amount of lattice impurities, and the impurity minerals were mainly biotite, zircon and chalcopyrite; the comprehensive evaluation conclusion was that the quality of the sample did not meet the requirements for use as high-purity quartz sand for photovoltaic crucibles, and the quartz ore source was unqualified.

[0059] The ICP-OES test results of sample 2 were 76ppm aluminum, no boron detected, no chromium detected, 1.2ppm manganese, 6.5ppm iron, no copper detected, 3.4ppm potassium, 1.7ppm lithium, 4.0ppm sodium, 1.2ppm nickel, 0.3ppm magnesium, 6.4ppm calcium, 0.9ppm titanium, and 16ppm zirconium. The infrared spectrum test results showed that the hydroxyl content was 11.65ppm. The polarizing microscope test results showed that the gas-liquid inclusions were 0-10μm (<10) / mm 2 , 10-20μm(<5) / mm2 , 20-30μm(<5) / mm 2 ; The electron probe test results show that there are fewer lattice impurities in quartz, and the main impurity mineral is only zircon; the comprehensive evaluation conclusion is that the quality of the sample is qualified for use as high-purity quartz sand for photovoltaic crucibles, and the quartz ore source is qualified.

[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for evaluating a high-purity quartz ore source for a photovoltaic crucible, characterized in that: S1. The surface of the block quartz raw material is cleaned and crushed into powder raw material, and after being digested with hydrofluoric acid and nitric acid, the content of metal impurity elements is detected using ICP-OES equipment; S2. After cleaning the surface of the block quartz raw material, cutting it into slices and polishing the surface, and performing FTIR infrared spectroscopy detection; S3. After cleaning the surface of the bulk quartz raw material, cutting it into slices and polishing the surface, and performing polarizing microscope inspection; S4. After cleaning the surface of the bulk quartz raw material, cut it into slices and polish the surface, and perform electron probe detection.

2. As claimed in claim 1, characterized in that The mesh size of the powder material crushed in step S1 is between 40-1000 meshes.

3. As claimed in claim 1, characterized in that The impurity elements detected in step S1 include aluminum, boron, chromium, manganese, iron, copper, potassium, lithium, sodium, nickel, magnesium, calcium, titanium, zirconium and phosphorus; the element content detection range is between 0.1-200ppm.

4. As claimed in claim 1, characterized in that In step S2, the thickness of each quartz slice is measured, and the preferred thickness is 1-5 mm.

5. As claimed in claim 1, characterized in that In step S2, the dried ore slices are tested using a Fourier transform infrared spectrometer in the wavelength range of 1000-4000. The hydroxyl determination formula is: ( T ) = kdC, In the formula, T is the transmittance of the quartz ore slice; k is a constant that is related to the properties of the absorbing substance and the wavelength of the incident light; d is the thickness of the specimen, in millimeters (mm) for each piece; C is the hydroxyl content of the sample, expressed in micrograms per gram.

6. As claimed in claim 1, characterized in that In steps S3 and S4, the thin slice is polished with polishing papers and polishing cloths of different mesh sizes, preferably with polishing cloths of 200 mesh, 6000 mesh, 1200 mesh and 2000 mesh, respectively.

7. As claimed in claim 1, characterized in that The preferred thickness of each quartz slice in step S3 is 50-300 μm.

8. As claimed in claim 1, characterized in that In step S3, the polarizing microscope measurement mode is transmission polarization.

9. As claimed in claim 1, characterized in that In step S4, the occurrence state of the impurity minerals is analyzed, including strip, dot, line, layer, block, etc.

10. The method according to claim 1, wherein: Through step S1 and step S4, the element ratio of the impurity minerals in the quartz slice is calculated, and then the mineral composition is determined.

Citation Information

Patent Citations

  • Method for discriminating industry performance of natural crystalline silica

    CN101183094A

  • Method for processing 4N high-purity quartz by utilizing vein quartz as raw material

    CN102887519A

  • Preparation method of high-quality quartz sand and high-quality quartz sand

    CN115646635A

  • Sample preparation method for analyzing hydroxyl content in quartz ore

    CN116609143A

  • Method for determining occurrence state of impurity elements in quartz raw material

    CN116718624A